Human rights approaches to climate change : challenges and opportunities - Atapattu, Sumudu A. (Routledge research in international environmental law, 2016)
"While there is a clear link between climate change and human rights with the potential for virtually all protected rights to be undermined as a result of climate change, its potential catastrophic impact on human beings was not really understood as a human rights issue until recently. This book examines the link between climate change and human rights in a comprehensive manner. It looks at human rights approaches to climate change, including the jurisprudential bases for human rights and the environment, the theoretical framework governing human rights and the environment, and the different approaches to this including benchmarks. The human rights implications of international environmental law principles in the climate change regime are discussed. It explores how the human rights framework can be used in relation to mitigation, adaption, and adjudication. Other chapters examine how vulnerable groups - the poor, women, and indigenous peoples - would be disproportionately affected by climate change. The book then goes on to discuss new categories of people created by climate change, those people who will be rendered stateless as a result of states disappearing and displaced by climate change, and whether human rights law can adequately address these emerging issues"--